Examining Online Grocery Purchase Intentions through an Extended TAM Framework : A Mediation Analysis Approach - Mahadevan, Kala; Punjani, Krunal K.; Joshi, Sujata (Indian Journal of Marketing, 2023)
Purpose : The present study has attempted to extend the TAM framework for online grocery shopping (OGS) by adding convenience (CON) and subjective norms (SN) as exogenous constructs and examines direct and sequential mediation among CON, SN, perceived ease of use (PEOU), perceived usefulness (PU), attitude toward (ATT) OGS, and online grocery purchase intention (OGPI). Methodology : This study proposed a conceptual model for OGS, for which data from 453 respondents across India were collected. Furthermore, this study employed a sequential mediation approach and tested the proposed constructs’ direct relationships. Findings : This study revealed that CON significantly impacted PEOU and PU, while PEOU significantly influenced PU and ATT. SN also influenced PU. Additionally, PU significantly affected ATT, and ATT influenced OGPI. Moreover, PU and ATT as sequential mediators significantly affected the relationships among SN–OGPI, PEOU–OGPI, and CON–OGPI, out of which complete mediation was found for PEOU–PU–ATT–OGPI, and the other two were partial mediation. Furthermore, CON–PEOU–ATT–OGPI was also found to have partial sequential mediation. This study added to the literature on OGS by extending TAM with SN and CON, a hitherto under-researched area in this domain. Practical Implications : The study had practical implications for e-retailers. Grocery e-retailers need to focus on the CON aspects of consumers. Additionally, website design characteristics need to be focused on, which in turn would have an impact on the PEOU of the website, which would favorably impact consumer ATT OGS. Originality : This study sought to address a critical gap in the research literature on OGS by examining the collective impact of SN and CON on the TAM constructs.